Recent progress in performance optimization of Cu-SSZ-13 catalyst for selective catalytic reduction of NOx - Li, Pan; Xin, Ying; Zhang, Hanxue; Yang, Fuzhen; Tang, Ahui; Han, Dongxu; Jia, Junxiu; Wang, Jin; Li, Zhenguo; Zhang, Zhaoliang (Frontiers in Chemistry, 2022)
Graphical Abstract Table of Contents.